Enhanced growth performance, haemato-biochemical and immune parameters of Asian seabass, Lates calcarifer (Bloch, 1790) fed dietary supplementation with Polygonum chinense - Abdul Razak, Rashidah; Mohamed Din, Mohamed Shariff; Md. Yusoff, Fatimah; Ismail, Intan Safinar (Asian Fisheries Society, 2019)
The present study evaluated the effects of Polygonum chinense extract (PCE) on the growth performance, haemato-biochemical and innate immunity parameters of Asian seabass, Lates calcarifer (Bloch, 1790). The fish with an average weight of 9.5 ± 0.2 g were fed for 60 days using three supplementation diets of PCE at 0.2 %, 0.5 % and 1.0 %, and a non-supplemented diet as a control. Fish fed on 0.5 % PCE diet revealed significant higher body weight gain, specific growth rate, protein efficiency ratio, condition factor, and significantly lower feed conversion ratio. Dietary supplementation with 0.5 and 1.0 % showed a significant increase in red blood cell count and haemoglobin level, but the white blood cell count significantly increased only in 1.0 % diet. The alkaline phosphatase level significantly increased in fish group fed 0.2 and 0.5 % diets, but the aspartate transaminase level significantly decreases in 0.2 and 1.0 % groups. Meanwhile, all PCE supplemented diets showed significant increase in total protein, albumin, globulin, albumin: globulin ratio, total immunoglobulin, lysozyme, respiratory burst and phagocytic activities, and significantly reduced the alkaline transaminase level. These results suggest that dietary P. chinense supplementation at 0.5 % was found to be suitable to enhance the growth performance and immune status of Asian seabass.